How does Corporate Environmental Performance Impact the Stock Performance of Finnish Firms? Implications for Sustainability - Dutta, Probal; Dutta, Anupam; Bouri, Elie (Palgrave Macmillan, 2024)
This study examines the relationship between corporate environmental performance (CEP) and corporate financial performance (CFP) in Finland. Based on the data from 21 large Finnish companies listed on the Nasdaq Helsinki, a linear regression model is developed for inquiring into the connection between CEP and CFP. After controlling for the effect of four variables namely, profitability (ROA), leverage (debt-to-equity ratio), research and development intensity (research and development expenses divided by total sales) and growth (percentage change in sales), the current study finds that better CEP contributes to better CFP even in a civil law country like Finland and even if the quantitative measure so CEP are employed in the analysis. GHG emissions emerge as the most important proxy of CEP, having a significant influence on the stock market returns, no matter the way GHG emissions are used in the generic regression model (i.e., amount of GHG emissions, reduction in GHG emissions, or ratio of GHG emissions to sales revenues), whereas water consumption, in all cases, has no significant impact on stock returns. Waste production and energy consumption also emerge as factors having significant influence on the stock market returns if certain measures of CEP are employed (e.g., absolute amount of and reduction in the amount of waste production, and reduction in the amount of energy consumption). Our analysis has important implications for policymakers and investors.
Keywords: Corporate environmental performance; Finnish firms; Stock returns; GHG emissions; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|